DAMPAK KENAIKAN JUMLAH PENDUDUK TERHADAP TINGKAT PENGANGGURAN TERBUKA DI KOTA SERANG TAHUN 2022-2023 - Akbar Maulana, Muhammad; Kusumoningtyas, Anggi Anggraeni (PRAJA: Jurnal Ilmiah Pemerintahan, 2025)
This research aims to determine local government governance in waste management in Palembang City. The research used is a qualitative approach due to the characteristics of the research which aims to describe answers to questions and analyze them regarding local government governance in Palembang City, especially in Kalidoni District, so that an understanding and analysis of the factors that play a role in it is obtained. Based on the previous discussion, the conclusions from the results of research conducted regarding waste management in Kalidoni District, Palembang City: the issues and potential solutions viewed from a government governance perspective are as follows: 1) Solid waste governance in Palembang City as follows: In general, the pattern of waste management in other large cities in Indonesia is still focused on the performance of the Regional Government in managing waste with the concept: transportation from TPS to TPA. Next, it is dumped in the landfill using the open dumping concept. Waste management in Palembang City also found waste management concepts using the 3R system and Waste Bank, although the amount is still small and has not significantly helped reduce the volume of waste in Palembang City, which amounts to more than a thousand tons per day. 2) Waste management in Kalidoni District was developed from the perspective of government governance in Palembang City, consisting of: a) Leaders and Leadership, one of the potential determining aspects of government governance.